Improving structure and transparency in reliability evaluations of data under REACH: suggestions for a systematic method. Issue 1 (2nd January 2020) - Ingre-Khans, Ellen; Ågerstrand, Marlene; Rudén, Christina; Beronius, Anna
Abstract: The goal of identifying hazardous chemicals registered under the Registration, Evaluation, Authorization and restriction of CHemicals (REACH) Regulation and taking appropriate risk management measures relies on robust data registrations. However, the current procedures for European chemical manufacturers and importers to evaluate data under REACH neither support systematic evaluations of data nor transparently communicate these assessments. The aim of this study was to explore how using a data evaluation method with predefined criteria for reliability and establishing principles for assigning reliability categories could contribute to more structured and transparent evaluations under REACH. In total, 20 peer-reviewed studies for 15 substances registered under REACH were selected for an in-depth evaluation of reliability with the SciRAP tool. The results show that using a method for study evaluation, with clear criteria for assessing reliability and assigning studies to reliability categories, contributes to more structured and transparent reliability evaluations. Consequently, it is recommended to implement a method for evaluating data under REACH with predefined criteria and fields for documenting and justifying the assessments to increase consistency of data evaluations and transparency.